Kebutuhan Informasi Narapidana Narkotika dalam Proses Rehabilitasi Sosial di Lembaga Permasyarakatan Kelas I Tangerang - Nuristia, Maghfira; Azwar, Muhammad (Pustakaloka, 2023)
Abstract: Drugs abuse occurs based on the awareness of the perpetrator. Understanding of narcotics, legal norms, and even knowledge about oneself is the cause of narcotics abuse. Library materials can be a means in the rehabilitation process for narcotics prisoners in Correctional Institutions. This study employs descriptive method with qualitative approach, the main objective of this study is to find out   information needs of narcotics inmates at Tangerang Class I Penitentiary. As for the data collection technique, the researcher uses observations, interviews with seven informants, and documentation in order to obtain the data. The results shows that reason of drugs abuse is caused by three factors, i.e. personality factors, educational factors, and spanning population factors. Narcotic inmates need information with subjek fiction, religious, and general. Currently, the procurement of library materials in library is obtained only through grants from the National Library and the Regional Library of Tangerang City. The results of this study can be used as reference for conducting library books and library activities in the Library of Tangerang Class I Penitentiary in Tangerang.Keywords: information needs; narcotics inmates; social rehabilitation; Tangerang class I penitentiaryAbstrak: Penyalahgunaan narkotika terjadi berdasarkan kesadaran pelaku. Pemahaman mengenai narkotika, norma hukum, bahkan pengetahuan mengenai diri sendiri menjadi penyebab penyalahgunaan narkotika. Bahan perpustakaan dapat menjadi sarana dalam proses rehabilitasi narapidana narkotika di Lembaga Permasyarakatan. Metode penelitian yang digunakan adalah deskriptif dengan pendekatan kualitatif yang bertujuan mengetahui jenis kebutuhan informasi narapidana narkotika di Lembaga Permasyarakatan. Teknik yang digunakan dalam pengumpulan data adalah observasi, wawancara dengan tujuh informan, dan dokumentasi. Hasil penelitian menunjukkan penyebab penyalahgunaan narkotika terdiri dari tiga faktor, yaitu kepribadian, pendidikan, dan populasi yang rentan. Narapidana narkotika membutuhkan informasi dengan subjek fiksi, agama, dan umum. Saat ini pengadaan bahan perpustakaan hanya melalui hibah dari Perpustakaan Nasional dan Perpustakaan Daerah Kota Tangerang dan belum menyesuaikan dengan kebutuhan pemustaka. Hasil penelitian ini dapat digunakan sebagai bahan referensi dalam kegiatan pengadaan bahan perpustakaan dan kegiatan perpustakaan di Perpustakaan Lembaga Permasyarakatan Kelas I Tangerang.Kata kunci: narapidana narkotika; rehabilitasi sosial; Lembaga Permasyarakatan Kelas I Tangerang